2011
DOI: 10.1111/j.1744-6570.2011.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward Better Meta‐analytic Matrices: How Input Values Can Affect Research Conclusions in Human Resource Management Simulations

Abstract: Simulations and analyses based on meta‐analytic matrices are fairly common in human resource management and organizational behavior research, particularly in staffing research. Unfortunately, the meta‐analytic values estimates for validity and group differences (i.e., ρ and δ, respectively) used in such matrices often vary in the extent to which they are affected by artifacts and how accurately the values capture the underlying constructs and the appropriate population. We investigate how such concerns might i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(119 citation statements)
references
References 89 publications
(223 reference statements)
2
116
1
Order By: Relevance
“…However, with this advantage of the rank ordering selection method comes the downside of increased potential for adverse impact when cognitive ability testing is involved, as has been demonstrated in a considerable amount of research (e.g., Bobko, Roth, & Potosky, 1999;Cascio et al, 1991;Hunter, Schmidt, & Rauschenberger, 1977;Roth, Switzer, Van Iddekinge, & Oh, 2011;Sackett & Roth, 1991;Sackett, Schmitt, Ellingson, & Kabin, 2001). Organizations may favor a particular alternative (maximum performance vs. diversity) depending on the goals or the purposes of the selection.…”
Section: Methods For Determining the Selection Decision Point The Stmentioning
confidence: 99%
See 4 more Smart Citations
“…However, with this advantage of the rank ordering selection method comes the downside of increased potential for adverse impact when cognitive ability testing is involved, as has been demonstrated in a considerable amount of research (e.g., Bobko, Roth, & Potosky, 1999;Cascio et al, 1991;Hunter, Schmidt, & Rauschenberger, 1977;Roth, Switzer, Van Iddekinge, & Oh, 2011;Sackett & Roth, 1991;Sackett, Schmitt, Ellingson, & Kabin, 2001). Organizations may favor a particular alternative (maximum performance vs. diversity) depending on the goals or the purposes of the selection.…”
Section: Methods For Determining the Selection Decision Point The Stmentioning
confidence: 99%
“…Based on this matrix, Roth et al (2011) then generated predictor and job performance criterion data based on both the uncorrected and corrected matrices and for each matrix conducted a multiple regression analysis by regressing job performance on the predictor variables. Results showed that, as would be expected, using the corrected input matrix greatly increased the multiple correlation coefficient (R = .75 for medium-complexity jobs) compared to the multiple correlation coefficient based on the uncorrected input matrix (R = .48).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations